2010
DOI: 10.1016/j.cmpb.2010.02.003
|View full text |Cite
|
Sign up to set email alerts
|

A graphic user interface toolkit for specification, report and comparison of dose–response relations and treatment plans using the biologically effective uniform dose

Abstract: A toolkit (BEUDcal) has been developed for evaluating the effectiveness and for predicting the outcome of treatment plans by calculating the biologically effective uniform dose (BEUD) and complication-free tumor control probability. The input for the BEUDcal is the differential dosevolume histograms of organs exported from the treatment planning system. A clinical database is built for the dose-response parameters of different tumors and normal tissues. Dose-response probabilities of all the examined organs ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
(20 reference statements)
1
4
0
Order By: Relevance
“…The upper panel of Table 5 summarizes the values of the calculated radiobiological quantities averaged over the 24 patients for each treatment modality and their respective standard deviation. Overall, the average values of normalP+ and PB for the three modalities (approximately 57%–67%) were found to reasonably agree with other published data (31‐33) . Using a paired t ‐test (p < 0.05), it was found that there was a significant difference between the normalP+ values of VMAT and 3D CRT (p = 0.004), as well as between the values of VMAT and those of HT (p < 0.0001).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The upper panel of Table 5 summarizes the values of the calculated radiobiological quantities averaged over the 24 patients for each treatment modality and their respective standard deviation. Overall, the average values of normalP+ and PB for the three modalities (approximately 57%–67%) were found to reasonably agree with other published data (31‐33) . Using a paired t ‐test (p < 0.05), it was found that there was a significant difference between the normalP+ values of VMAT and 3D CRT (p = 0.004), as well as between the values of VMAT and those of HT (p < 0.0001).…”
Section: Resultssupporting
confidence: 85%
“…Once treatment planning was complete for each patient and each modality, the dose‐volume histograms (DVH) were exported from the respective TPS for each organ used in this study (namely: PTV, lungs, kidneys, orbits, heart, liver, thyroid, colon, and breasts for female patients only). Using an in‐house MATLAB (The MathWorks Inc., Natick, MA) program designed to radiobiologically evaluate different treatment plans or dose distributions, the traditional 3D CRT and both the VMAT and HT plans were be compared (32) . This program uses the previously discussed to calculate the respective radiobiological quantities for each plan.…”
Section: Methodsmentioning
confidence: 99%
“…The difference in these values was obtained to estimate the expected clinical impact of the differences obtained by the dosimetric analysis. A detailed presentation of the software that was used for the radiobiological analysis can be found in the work by Su et al Resulting TCP/NTCP calculated from doses reported by Pinnacle 3 were used as reference values when comparing to TCP/NTCP calculations from doses reported by VeriSoft. Tables report the summary of the model parameter values used for the examined cancer cases .…”
Section: Methodsmentioning
confidence: 99%
“…The tumor control probability (TCP) and normal tissue complication probability (NTCP) were calculated using an application previously developed at our institution to determine which plan would have the greatest therapeutic benefit. 23 The parameters used for calculating the TCP and NTCP values can be seen in Table 1, which were repeated from the work of Mavroidis et al . 24…”
Section: Methodsmentioning
confidence: 99%